Pengaruh Model Direct Instruction Berbantuan Simulasi Virtual Terhadap Pemecahan Masalah Fisika Peserta Didik - Baiq Ida Arianti; Hairunnisyah Sahidu; Ahmad Harjono; Gunawan Gunawan (Indonesian Journal of Applied Science and Technology, 2022)
Problem-solving ability is one of the essential competencies that students should develop in physics learning. However, classroom instruction is often focused on content delivery and routine exercises, resulting in limited opportunities for students to develop systematic problem-solving skills. This study aimed to investigate the effect of the Direct Instruction model assisted by virtual simulation on students' physics problem-solving ability. The study employed a quasi-experimental method using a non-equivalent control group design. The sample was selected through purposive sampling, consisting of 25 students in class X-MIA1 as the experimental group and 23 students in class X-MIA2 as the control group. Data were collected using a five-item essay test measuring physics problem-solving ability and analyzed using an independent-samples t-test with pooled variance and normalized gain (N-gain). The results showed that the mean score of the experimental group increased from 28.83 to 67.20, while the control group improved from 22.13 to 53.22. Hypothesis testing indicated that the calculated  (4.01) exceeded the critical t value (2.02) at the 5% significance level. Therefore, the Direct Instruction model assisted by virtual simulation had a significant positive effect on improving students' physics problem-solving ability.